2010
DOI: 10.1258/hsmr.2010.010008
|View full text |Cite
|
Sign up to set email alerts
|

The effect of work environment on intent to leave the nursing profession: a case study of bedside registered nurses in rural Florida

Abstract: The purpose of this research was to explore the effect work environment has on the intent to leave the profession for rural hospital bedside registered nurses (RNs). Subscales of autonomy, control over the practice setting, nurse-physician relationship and organizational support were incorporated into the analysis to determine which aspects of work environment directly affect the intent to leave the profession. An explanatory cross-sectional survey was distributed to 259 direct care bedside RNs employed at a r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 33 publications
4
10
0
Order By: Relevance
“…In the current study, nurses reported that they have limited opportunity to take part in policy decisions, a lack of freedom to make important patient care and work decisions, and limited participation in efforts to control costs. All these demonstrate limited or even lack of autonomy of nurses, consistent with other authors . Nurse limited or lack autonomy negatively reflect on nurse job satisfaction and retention .…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…In the current study, nurses reported that they have limited opportunity to take part in policy decisions, a lack of freedom to make important patient care and work decisions, and limited participation in efforts to control costs. All these demonstrate limited or even lack of autonomy of nurses, consistent with other authors . Nurse limited or lack autonomy negatively reflect on nurse job satisfaction and retention .…”
Section: Discussionsupporting
confidence: 89%
“…The overall mean of the hospital organizational characteristics indicates a low level of nurses’ views on hospital organizational characteristics. This indicates poor work environments as marked by low nurse professional autonomy, consistent with other studies; low nurse satisfaction and high nurse turnover, similar to Kutney‐Lee et al; low quality of work, consistent with Olds et al and Wei et al; and, in turn, low patient satisfaction, similar to Olds et al and Wei et al…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations